2009
DOI: 10.4314/aas.v1i1.45788
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of severe traumatic brain injury at a critical care unit: a review of 87 patients

Abstract: OBJECTIVE:To determine the outcome of severe traumatic brain injury and to document the factors influencing mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
4
16
0
Order By: Relevance
“…What is glaringly absent from all the articles written on TBI in Kenya, with the possible exception of the study by Gachanja, is what happens to those TBI patients who survive and are discharged from hospital. In other words, all scholarly literature available on TBI in Kenya pertains to the (hospital) treatment of people with brain injuries with no mention of any post-hospital rehabilitation services for TBI survivors, most of whom have moderate to severe limitations (Gachanja, 2013;Kiboi et al, 2011;Opondo & Mwangombe, 2007). As there are no outpatient brain rehabilitation programs affiliated with the hospitals such as KNH, and none in the private sector, TBI survivors in Kenya currently have nowhere to go for brain injury rehabilitation services such as cognitive rehabilitation that can enable them to gain an amount of independence and improve their quality of life, including obtaining employment when possible.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is glaringly absent from all the articles written on TBI in Kenya, with the possible exception of the study by Gachanja, is what happens to those TBI patients who survive and are discharged from hospital. In other words, all scholarly literature available on TBI in Kenya pertains to the (hospital) treatment of people with brain injuries with no mention of any post-hospital rehabilitation services for TBI survivors, most of whom have moderate to severe limitations (Gachanja, 2013;Kiboi et al, 2011;Opondo & Mwangombe, 2007). As there are no outpatient brain rehabilitation programs affiliated with the hospitals such as KNH, and none in the private sector, TBI survivors in Kenya currently have nowhere to go for brain injury rehabilitation services such as cognitive rehabilitation that can enable them to gain an amount of independence and improve their quality of life, including obtaining employment when possible.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In an article published in the Annals of African Surgery, Opondo and Mwangombe (2007) reported that their research was conducted on 87 patients with TBI admitted at KNH Intensive Care Unit (ICU) between April and September, 2005. Fifty-eight percent of the patients were involved in road traffic accidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Although mortality rate following TBI is higher than for the control group of 47.8%, the nature of patients admitted to our ICU varies widely, it being a multidisciplinary unit. Patients in respiratory failure from different causes who require ventilatory support, postoperative patients who require intensive monitoring and care, and stroke patients are among the array of patients managed in the unit.…”
Section: Discussionmentioning
confidence: 99%
“…About 33% of these patients remained in a persistent vegetative state. 1 It has been documented that morbidity and mortality following TBI is determined by the severity and presence of secondary injuries such as hypoxia, hypotension, hypercapnia, hyperglycaemia and acidosis. 2 Teasdale and Jennett 3 described the Glasgow Coma Scale, which was initially designed to assess the level of consciousness after TBI in a neurosurgical intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, 10.3% had good recovery, 8% had moderate disability, 8% had severe disability, 21.8% had persistent vegetative state and 54.0% died. The high mortality rate was related to the high frequency of multiple injuries and late presentation to the hospital (16). While in France, the highest GOS score was moderate disability followed severe disability and lastly good recovery with the global disability remaining high because of lack of rehabilitation center and follow up (15).…”
Section: Introductionmentioning
confidence: 99%